Accommodation: Its relation to refractive errors, amblyopia and biometric parameters - Maheshwari, R; Sukul, RR; Gupta, Y; Gupta, M; Phougat, A; Dey, M; Jain, R; Srivastava, G; Bhardwaj, U; Dikshit, S (Nepalese Journal of Ophthalmology, 2011)
Aim: To study accommodation in relation to different refractive errors, amblyopia and to measure the anatomical changes in the accommodating eye Materials and methods: We studied the amplitude of accommodation (AA) in 150 patients in the age group 11 – 30 years which included emmetropes, myopes, hypermetropes and hypermetropic amblyopes using the Royal Air Force (RAF) rule. The anterior chamber depth (ACD), axial length (AxL) and lens thickness (LT) changes during accommodation were measured using an A-scan. Myopes and hypermetropes were further divided based on the amount of refractive error : < 2D, 2 -4D and > 4D. Results: Corrected low myopes had the highest accommodation amplitude (p < 0.05) followed by emmetropes. Corrected hypermetropes were found to have the lowest amplitude of accommodation (p < 0.05). The amblyopic eye had a significantly low AA compared to the non-amblyopic eye (p < 0.05). ACD decreased (p < 0.05) and LT increased (p < 0.05) during accommodation. The AxL increase was maximum in myopes (p < 0.05) followed by hypermetropes but the change was not significant in hypermetropes (p > 0.05). Conclusion: The amblyopic eye has low amplitudes of accommodation proving the benefit of near adds in amblyopic patients. Prolonged near work might induce myopia in susceptible eyes by increasing the axial length. Key words: accommodation, refractive error, amblyopia, biometric changes DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5267 Nepal J Ophthalmol 2011; 3(2): 146-150